The growth in juvenile spectacled caimans at The Lost World of Tambun Malaysia - Rahman, Ramon; Fraser, Charisha Florence; Tumbelaka, Ligaya I.T.A. (ARSHI Veterinary Letters, 2024)
The spectacled caiman needs to be better studied, and its basic life history needs to be explored. Growth rates and changes in growth with age and size are essential life history characteristics. This study aimed to determine the growth rate of juvenile spectacled caimans in captivity and understand the factors that affect the growth rate of juvenile spectacled caimans. Fourteen juvenile spectacled caimans were used in the present study. The study shows that the growth rate of all the juvenile spectacled caimans varied, where specimens such as Delta and 9th Dot had the highest growth rate in terms of weight at 0.98 g/day and 0.89g/day, respectively. However, Little Foot had the lowest growth rates in snout-vent length and weight parameters at 0.03 cm/day and 0.08 cm/day. This study shows that the growth rate of juvenile spectacled caimans that dominance has a strong effect on the growth rate of juvenile spectacled caimans in captivity. Other factors that could be affected were social behavior, feeding behavior, and natural selection.